Female Labor Supply and Child Care: In the case of Urban Young Couple with Pre-school Children - Premaratne, S.P. (My University, 2011)
it is well-known in micro econometric literature that the labour supply of young couples with young children differs surprisingly from the rest of the labour force (Chiuri 1999). The presence of very young children is highly significant for household (HH) labour supply decisions (Bloemen and Stancanelli 2008, Rammohan and Whelan 2005). The area is not quite researched in a country like Sri Lanka. With dramatic changes in socio economic situation, and as a result of urbanization, the traditional extended family culture in Sri Lanka has been converted to a nuclear family culture. With the change in socio economic life style of the society, HH environment has changed and both parents work. Thus, child caring has become a real concern. Over the last decade, the cost of child caring has increased.